Control of herbicide resistant Limnocharis flava (L.) Buchenau using herbicides mixtures - Juraimi, Abdul Shukor; Sahid, Ismail; Man, Azmi; Shari, Erwan (2008)
Limnocaris flava (L.) Buchenau (Yellow bur head) is an important broadleaf weed in rice fields (Azmi 2003). This weed spreads throughout South East Asia especially in the rice crop (Azmi 2003). It has been reported resistance to 2,4-D and metsulfuron methyl in Indonesia and Malaysia respectively (Heap 2005). Herbicide mixture may help to prevent resistance problem as well as shifts in weed population which is always associated with the use of a single herbicide (Wrubel and Gressel 1994). Little study has been conducted to determine the effect of herbicide combination to control biotype resistant of L. flava in Malaysia. The purpose of this study was to determine the effect of bensulfuron-methyl, bentazon sodium/MCPA dimethyl, singly or in combination on resistant biotype of L. flava. A field experiment has been conducted in 2006 at weed experimental Plot, MARDI Stesyen, Seberang Prai, Penang, Malaysia to control herbicide resistance biotype of Limnicharis flava (L.) Buchenau using bensulfuronmethyl and bentazon sodium/MCPA dimethyl. The 5 weeks old plants were treated with single herbicide or a combination of the two herbicides. The herbicide rates used were half of recommended rate, recommended rate and double recommended rate. The results shows that bentazon-sodium/MCPA dimethyl at the recommended (0.74 kg a.i/ha) or higher rates alone controlled biotype R of L. flava effectively. Bensulfuron-methyl alone at all rates did not control L. flava. Of all tank-mix combination treatments of bentazon sodium/MCPA dimenthyl and bensulfuron-methyl, three antagonistic and six additive joint actions were observed.